2017
DOI: 10.3390/ijerph14121521
|View full text |Cite
|
Sign up to set email alerts
|

Building-Based Analysis of the Spatial Provision of Urban Parks in Shenzhen, China

Abstract: Urban parks provide important environmental, social, and economic benefits to people and urban areas. The literature demonstrates that proximity to urban parks is one of the key factors influencing people’s willingness to use them. Therefore, the provision of urban parks near residential areas and workplaces is one of the key factors influencing quality of life. This study designed a solution based on the spatial association between urban parks and buildings where people live or work to identify whether people… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…For quantity, studies in Chinese cities show more cases of inequity-high-SES people have higher quantities of green space than low-SES [75,76,78,81,93,95,98,99,102,104]-than equity [12,82] or mixed findings [45,74]. Studies in other Asian cities such as Sheikhupura, Pakistan [69], Tehran, Iran [71,84], and Hamadan, Iran [46] also found inequitable results for green space quantity.…”
Section: Results: Do Inequities In the Global South Vary Based On Geomentioning
confidence: 98%
“…For quantity, studies in Chinese cities show more cases of inequity-high-SES people have higher quantities of green space than low-SES [75,76,78,81,93,95,98,99,102,104]-than equity [12,82] or mixed findings [45,74]. Studies in other Asian cities such as Sheikhupura, Pakistan [69], Tehran, Iran [71,84], and Hamadan, Iran [46] also found inequitable results for green space quantity.…”
Section: Results: Do Inequities In the Global South Vary Based On Geomentioning
confidence: 98%
“…At the community park level, the distribution of underserved communities is scattered throughout the whole city, but clustered at the city park level. The disparity analysis showed that the mismatch between park provision and demand population is better in core districts (Luohu, Futian, Nanshan, and Yantian) than that in non-core districts [76]. Communities, which suffer from a severe shortage of park service provision due to the high population density as well as the low spatial accessibility, were located in Songgang, Shajing, Fuyong, Xixiang, and Xin’an in Bao’an District; Gongming in Guangming District; Guanlan and Longhua in Longhua District; and Pinghu, Bantian, and Buji in Longgang District.…”
Section: Discussionmentioning
confidence: 99%
“…Any attempt to statistically evaluate the strength of association between urban elements and PM 2.5 pollution will be complicated by a range of confounding factors (7), thus data screening should be undertaken in studies of daily PM 2.5 concentrations to screen for specific pollution events (11,13,38). Figure 1 shows the distribution of PM 2.5 concentration increase per hour from UTC+7 time zone to UTC+9 time zone 1 http://106.37.208.233:20035/ for a total of 283 cities (Karamay and Urumqi, the only two cities in UTC+6 time zone are not considered) (The detailed average hourly trends of PM 2.5 concentration in each city are shown in Figure S1). In most cities, PM 2.5 concentration exhibits a bimodal pattern of changing rhythms, peaking around dawn and dusk, relatively stable at night.…”
Section: Research Design Dependent Variable: Pm 25 Datamentioning
confidence: 99%
“…With the rapid urbanization and economic development, urban greening has become an urban livability standard and important symbol of residents' well-being ( 1 ). How to achieve a win-win situation for environmental protection and urban development has long been controversial for policymakers ( 2 ).…”
Section: Introductionmentioning
confidence: 99%